The Role of Pancasila as the Legal Basis in Indonesia - Praditya, Farda Putri (Jurnal Scientia Indonesia, 2017)
Pancasila as the basis of the country of Indonesia was the foundation and guidelines for the nation’s social life in Indonesia, a nation and a country to achive the goal and his ideals. Pancasila was also made as a Foundation is at once the source of law in Indonesia. As a source of law in Indonesia, Pancasila was footing informing all rules that exist. This means that the current regulations include the values of the godhead, humanitarian and development in accordance with the Pancasila. Indonesia society that continuously change from time to time make laws which now continues to undergo changes in accordance with the times and the dynamics of the community. Therefore, the Pancasila will be standard of every change and development of the society especially in the process of formation of the militate invitation in Indonesia because of Pancasila as the legal in law order in Indonesia’s most high position.